2017
DOI: 10.1093/nar/gkx012
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble simulations: folding, unfolding and misfolding of a high-efficiency frameshifting RNA pseudoknot

Abstract: Massive all-atom molecular dynamics simulations were conducted across a distributed computing network to study the folding, unfolding, misfolding and conformational plasticity of the high-efficiency frameshifting double mutant of the 26 nt potato leaf roll virus RNA pseudoknot. Our robust sampling, which included over 40 starting structures spanning the spectrum from the extended unfolded state to the native fold, yielded nearly 120 μs of cumulative sampling time. Conformational microstate transitions on the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Computational studies have predicted that PKs fold through diverse mechanisms, depending on their sequence, by parallel pathways, cooperatively in an all-or-none manner, or by a combination of both mechanisms, exploring several intermediate states, some of which contain nonnative base pairing or alternate structures ( 18 , 41 47 ). The principle that assembly routes of PKs depend on the stabilities of individual secondary structural elements ( 18 ) explains the diversity of the folding mechanisms of PK.…”
mentioning
confidence: 99%
“…Computational studies have predicted that PKs fold through diverse mechanisms, depending on their sequence, by parallel pathways, cooperatively in an all-or-none manner, or by a combination of both mechanisms, exploring several intermediate states, some of which contain nonnative base pairing or alternate structures ( 18 , 41 47 ). The principle that assembly routes of PKs depend on the stabilities of individual secondary structural elements ( 18 ) explains the diversity of the folding mechanisms of PK.…”
mentioning
confidence: 99%
“…However, many biomolecules exhibit short-lived intermediates in their folding trajectory with microsecond lifetimes; prime examples are metastable intermediates of small folding proteins, 49 partially open intermediates associated with membrane transporters, 50 and pseudoknots in oligonucleotides. 51 Such metastable states have typical lifetimes of some tens of microseconds but cannot be detected directly. In Figure 5a, we show a simulated timetrace of an oligonucleotide that exchanges between three conformations on microsecond time scales.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the WNV stimulatory structure, which causes an extremely high frameshifting efficiency (up to 70%) [27] , shows extensive conformational plasticity [32] . The alternative folding propensity of stimulatory structures has also been identified in other viruses, such as the turnip crinkle virus [28] , the potato leaf roll virus [30] , and the recently identified SARS-CoV-2 [33] , [90] , through various methods. These results suggest that conformational plasticity is a common feature for most, if not all, frameshift-stimulating RNA structures.…”
Section: Mechanisms Of −1 Prf Involving Conformational Dynamics Of Mrnamentioning
confidence: 99%
“…An increasing body of evidence has shown that in addition to structural stability, the conformational dynamics of an mRNA structure play a key role in the stimulatory effects on ribosomal frameshifting [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . In addition, ribosomes and tRNA also undergo profound conformational changes during translocation [34] , [35] , though how their structures are involved in −1 PRF remain unclear.…”
Section: Introductionmentioning
confidence: 99%